Pewarnaan Titik Ketakteraturan Lokal Inklusif pada Hasil Operasi Comb Graf Bintang - Arika Indah Kristiana; Surya Indriani; Ermita Rizki Albirri (Universitas Airlangga, 2022)
Let G(V,E) is a simple graph and connected where V(G) is vertex set and E(G) is edge set. An inclusive local irregularity vertex coloring is defined by a mapping l:V(G) à 1,2,…, k as vertex labeling and wi : V(G) à N is function of inclusive local irregularity vertex coloring, with wi(v) = l(v) + ∑u∈N(v) l(u). In other words, an inclusive local irregularity vertex coloring is to assign a color to the graph with the resulting weight value by adding up the labels of the vertices that are neighbouring to its own label. The minimum number of colors produced from inclusive local irregularity vertex coloring of graph G is called inclusive chromatic number local irregularity, denoted by Xlisi(G). In this paper, we learn about the inclusive local irregularity vertex coloring and determine the chromatic number of comb product on star graph.